Rheumatic Heart Disease In School Going Children: A Study From Lumbini Province, Nepal - Samir Gautam; Sachin Dhungel; Bishal KC; Mazhar Khan; Santosh Shah (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Rheumatic Heart Disease is declining from developed countries but still is important cause of morbidity and mortality in under- developed and developing countries.MATERIAL AND METHODS It was a prospective observational study conducted at Lumbini Province Nepal. Seven thousand six hundred and fourty school going children were evaluated to look for presence of Rheumatic Heart Disease.RESULTS Out of total 7640 school going children 56.6% were male and 43.4% were female. Majority (74%) of children evaluated belonged to Government school. Most of the children (54.7%) were of more than 10 years of age. Clinically murmur was present in 8.9%. RHD was found in total 14 children with prevalence of 1.83 per thousand children. RHD was more common in female (64%) than male (36%). Most common valve involvement was Mitral valve and most common lesion was Mitral Stenosis.CONCLUSION RHD is still of major health concern among school going children in Lumbini Province Nepal. Strategies to reduce its occurrence in the community is important to reduce its complications.